Magnitude of Intestinal Parasitosis, Malnutrition, and Predictors of Anemia Among Nonpregnant Reproductive-Age Women Attending Healthcare Services in Olenchity General Hospital, Central Ethiopia - Yada, Tesema Abera; Dessie, Yadeta; Darghawth, Rasha; Wilfong, Tara; Kure, Mohammed Abdurke; Roba, Kedir Teji (Frontiers in Tropical Diseases, 2021)
Abstract Background: Anemia and malnutrition remain public health challenge in developing world. Anemia during non-pregnant state is one of the neglected medical condition affecting reproductive age women around the world. Globally, it is estimated that one-third of all of reproductive age women are anemic. Although it has negative consequences and extensive burden, anemia in non-reproductive age women are rarely studied in African. In Ethiopia, studies investigating anemia and malnutrition among non-pregnant reproductive age women is limited. Therefore, this study was aimed to assess intestinal parasitic infection, malnutrition and predictors of anemia among non-pregnant reproductive age women in Olenchity hospital, central Ethiopia. Methods: A facility based cross-sectional study design was employed among 405 non-pregnant reproductive age women in Olenchity hospital, central Ethiopia from 14th February to 24th March, 2018. Data were collected using a pretested interviewer administered questionnaire. A blood samples were collected and tested to determine hemoglobin level by using hematology analyzer machine. Collected data were entered in to Epi-data version 3.02 and exported to SPSS version 20 for analysis. Multivariable logistic regression was done to identify factors independently associated with anemia after controlling for possible confounders. P-value <0.05 was statistically significant. Result: Overall, the magnitude of anemia was found to be 47.4% [95% CI: 42.7, 52.6], of which 34.8% were mild, 11.4% were moderate and 1.2% were severely anemic. The magnitude of intestinal parasitic infection, wasting and overweight were 34.6%, 26.2% and 8.1% respectively. Having no formal education [AOR=2.25, CI (1.02, 4.97)], using 3-5 sanitary pads per day during menses [AOR=1.66 CI (1.02, 2.68)], history of chewing khat [AOR= 4.45, CI (1.18, 16.83)], Being from households with mild food insecurity [AOR=3.41, CI (1.10, 10.58)] and having intestinal parasitic infection [AOR=2.28, CI (1.39, 3.47)] were factors independently associated with anemia. Conclusion: The magnitude of anemia, malnutrition and intestinal parasitic infection among non-pregnant reproductive age women were a considerable public health problem. Attention should be given to non-pregnant reproductive age women visiting healthcare services to reduce risks of anemia and malnutrition for the benefit of the women’s health. Deworming of non-pregnant reproductive age women is also very crucial.